The Application of E-Government Through the e-Gov Portal Application In Improving The Work Discipline of Civil Servants at the Communication and Informatics Office of Tangerang City - Audian Alfajar; Hilman Hilman; Machrunnisa Machrunnisa (Peneliti.net, 2023)
This qualitative research aims to find out about the application of the e-gov portal application in improving the work discipline of ASN Tangerang City, as well as understanding the obstacles that occur in the application of the e-gov portal application in improving the work discipline of ASN Tangerang City, especially at the Office of Communication and Information. This research method uses descriptive qualitative research methods. The research site is the Communication and Informatics Office of Tangerang City. The research subjects were the Head of the Application Maintenance & Implementation Section, employees, Computer Programmers. Data collection techniques used were observation, interview, documentation and triangulation. Data analysis techniques by reducing data or summarizing the data obtained, then by presenting data that has a relationship with the title then by drawing conclusions. In the application of e-government according to the results of research and studies from the Harvard JFK School of Government (Indrajit, 2016: 11),